AB0014 Nanoparticles as MRI Contrast Agent for Early Diagnosis of RA: Effects of Amino-PVA-Coated SPIONS on CD4+ T Cell Activity. (15th July 2016) - Strehl, C.; Maurizi, L.; Hermann, S.; Häupl, T.; Hofmann, H.; Buttgereit, F.; Gaber, T.
Abstract : Background: In medical applications nanotechnology provides new opportunities for diagnostic and therapeutic interventions in a variety of human diseases. Superparamagnetic iron oxide nanoparticles (SPION) are used as high-sensitive enhancer for magnetic resonance imaging, where they represent a promising tool for early diagnosis of destructive diseases such as rheumatoid arthritis (RA) and osteoarthritis (OA). However, safety aspects still represent crucial problems for the further development of nanotechnology based products. Therefore, the focus of our work here was to identify more in detail putative unwanted effects of amino-polyvinyl alcohol-coated (a-PVA) SPION on human immune cell functions. Objectives: Since we could demonstrate in former studies that professional phagocytes are activated by a-PVA-SPION, we here focused on the influence of these nanoparticles on human T helper cell activity. Methods: PBMCs were isolated from blood samples obtained from healthy donors (HD, n≥9) or patients suffering from RA (n≥11). Primary human CD4 positive T cells were separated via MACS-Sort and incubated with the mitogen PHA-L (5μg/ml) and/or varying doses of a-PVA-SPION (1 μg/ml, 10 μg/ml, and 100 μg/ml) or left untreated for 20 h (analysis of caspase-3/7-activity, intracellular ATP content and CD25 expression) or 72 h (analysis of proliferation and CD25 expression). Cells were incubated under either normoxia (app. 18%O2) or hypoxia (1%O2) in order to mimic conditions found in the circulation and in the inflamed joint, respectively. Results: We observed for PHA-L/a-PVA-SPION co-stimulated T cells from HD a decrease in cell count (all p<0.05) whereas the caspase-3/7-activity is increased (all p<0.05) in these samples, as expected. Although, we observed that T cells from RA patients are more susceptible to low-dose a-PVA-SPION-induced apoptosis than T cells from HD (p<0.05), in both groups a-PVA-SPION do not activate CD4+ T cells per se and do not influence mitogen-mediated T cells activation with regard to CD25 expression and cell proliferation. Nevertheless, we were able to demonstrate that CD4+ T cells obtained from RA patients and healthy subjects differ in their response to mitogen stimulation and oxygen availability. Conclusions: PVA-SPION at concentrations up to 100μg/ml do neither activate nor significantly influence mitogen-stimulated CD4+ T cells activation and have negligible influence on T cells apoptosis. Disclosure of Interest: None declared